ANALISIS TARI SILAMPARI KAYANGAN TINGGI (Studi Etnografi Di Kota Lubuklinggau) - Isbandiyah, Supriyanto (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2025)
ABSTRACT This research was carried out with the aim of finding out and analyzing the meaning of the Silampari Kayangan Tinggi Dance which is part of the culture of the people of Lubuklinggau City, both the meaning of the clothes they wear and the meaning of their movements, as well as analyzing the values of local wisdom contained in the Silampari Kayangan Tinggi Dance. The method used is qualitative with an ethnographic study approach that does not only rely on documentation studies but also with field studies as supporting such as in-depth interviews. Informants were selected based on criteria while data analysis was carried out using qualitative data analysis techniques that have been developed by Spradley. For the validity of the data, the truth will be tracked through triangulation techniques. The results of the study show that (1) the clothes used in the Silampari Kayangan Tinggi Dance symbolize politeness, politeness, and ethics when welcoming guests. (2) The resulting Silampari Kayangan Tinggi Dance Movement is a movement that contains values, namely gentleness and consistency. Dance movements are divided into two, namely meaningful movements and pure movements. Meaningful motion is motion that contains a clear meaning, while pure motion is motion that describes something symbolically. (3) The Silampari Kayangan Tinggi Dance contains local wisdom values that can be applied in daily life, including the values of manners, gentleness, consistency, privilege of guests, mutual respect, mutual respect, humility, care, harmony or familiarity, patience, responsibility and cooperation. Keywords: Silampari Kayangan Tinggi Dance and Value of Local Wisdom